2022
DOI: 10.1126/scitranslmed.abm6420
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1-2 trial of sitravatinib and nivolumab in clear cell renal cell carcinoma following progression on antiangiogenic therapy

Abstract: The accumulation of immune-suppressive myeloid cells is a critical determinant of resistance to anti–programmed death-1 (PD-1) therapy in advanced clear cell renal cell carcinoma (ccRCC). In preclinical models, the tyrosine kinase inhibitor sitravatinib enhanced responses to anti–PD-1 therapy by modulating immune-suppressive myeloid cells. We conducted a phase 1-2 trial to choose an optimal sitravatinib dose combined with a fixed dose of nivolumab in 42 immunotherapy-naïve patients with ccRCC refractory to pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 43 publications
1
24
1
Order By: Relevance
“…Furthermore, recent studies revealed some unique characteristics of sitravatinib. Sitravatinib possesses the ability to reduce immunosuppressive myeloid cells and potentiate immune checkpoint blockade in preclinical and clinical models [ 22 , 23 ]. The combination of sitravatinib and anti–programmed death-1 (PD-1) therapy has demonstrated high clinical activity with manageable toxicity in oral cavity cancer and renal cancer [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, recent studies revealed some unique characteristics of sitravatinib. Sitravatinib possesses the ability to reduce immunosuppressive myeloid cells and potentiate immune checkpoint blockade in preclinical and clinical models [ 22 , 23 ]. The combination of sitravatinib and anti–programmed death-1 (PD-1) therapy has demonstrated high clinical activity with manageable toxicity in oral cavity cancer and renal cancer [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sitravatinib possesses the ability to reduce immunosuppressive myeloid cells and potentiate immune checkpoint blockade in preclinical and clinical models [ 22 , 23 ]. The combination of sitravatinib and anti–programmed death-1 (PD-1) therapy has demonstrated high clinical activity with manageable toxicity in oral cavity cancer and renal cancer [ 22 , 23 ]. Sitravatinib has also been shown to block the chemotherapeutic drug efflux function of ABCB1 and ABCG2 at submicromolar concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent basic study showed novel histone methyltransferase EZH2 inhibitor can further reduce progression of urothelial carcinoma [32]. A translational study showed that combination therapy with the novel TKI sitravatinib and the anti-PD-1 immune checkpoint inhibitor improved the median progression-free survival for patients with kidney cancer [33]. Widespread availability of novel and favorable treatments can be appreciable at the population level to reduce the mortality rate of patients with all three cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Despite several successful applications, such as the recent trial examples of Tidwell et al (2021) [35] and Msaouel et al (2022) [36], the use of model-based phase I-II designs has been fairly limited. One major reason for this limited use is that these designs are statistically and computationally complicated.…”
Section: Dose Optimization For Car T-cell Therapiesmentioning
confidence: 99%